Continuous Integration and Delivery of Software products: Pipeline implementation (International Journal of Engineering and Computer Science, 2024)
Continuous practices, i.e., continuous integration, delivery, and deployment, are the software development industry practices that enable organizations to frequently and reliably release new features and products. CI/CD is the best practice for teams using a DevOps methodology and is best suited to agile methodologies. CI/CD automates code integration and delivery, allowing software development teams to focus more on business requirements. Implementing CI/CD and automating the delivery process from application development to the live environment using pipelines, reducing the time and errors during manual delivery, the previously mentioned high-quality and reliable software products are delivered to the end user.This work will automate the workflow of software products from development to supply and delivery using pipelines.